Doing counseling research - Ismail, Issham; Ahmad Shah, Wan Mahzom (Penerbit UTM, 1999)
This book was translated from English to Malay. The Chapter 1 defines research and discusses the importance of research to a counselor. Other topics covered are research process, systematic inquiry, etc.